Omics profiles in chronic venous ulcer wound fluid: innovative applications for translational medicine. (July 2014) - Mannello, Ferdinando; Ligi, Daniela; Canale, Matteo; Raffetto, Joseph D
<x xml:space="preserve">Abstract</x> Chronic venous disease represents a healthcare problem due to high prevalence and recurrence rates. Studies on chronic venous ulcer wound fluid (CVUWF) have demonstrated increased inflammation and proteolysis which can cause tissue destruction and delayed healing. This review discusses: nearly all known metabolites discovered in the past 25 years in CVUWF studies; the omics approaches characterizing the microenvironment of human venous leg ulcers; and the use of biocompounds as prognostic biomarkers and as possible targets for therapeutic approaches. A biomarker is a biological compound that can be functional or non-functional, specific or non-specific in the diagnosis/prognosis to a disease state and may be quantified to determine progression or regression of disease. Omics studies in CVUWF provide the impetus for future identification of biomarkers within the intricate network in chronic venous disease and set the basis for determining the appropriate combination of molecules that are expressed with the healing status of venous leg ulcers.